If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3.5(3x + -8) = x Reorder the terms: 3.5(-8 + 3x) = x (-8 * 3.5 + 3x * 3.5) = x (-28 + 10.5x) = x Solving -28 + 10.5x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -28 + 10.5x + -1x = x + -1x Combine like terms: 10.5x + -1x = 9.5x -28 + 9.5x = x + -1x Combine like terms: x + -1x = 0 -28 + 9.5x = 0 Add '28' to each side of the equation. -28 + 28 + 9.5x = 0 + 28 Combine like terms: -28 + 28 = 0 0 + 9.5x = 0 + 28 9.5x = 0 + 28 Combine like terms: 0 + 28 = 28 9.5x = 28 Divide each side by '9.5'. x = 2.947368421 Simplifying x = 2.947368421
| -(3-15y)=12 | | -(6x-3)=-9 | | 3-6x=2+6x | | 1/3(12x-36)+4=x+25 | | 5k-3/2=4 | | 2b+5=b+13 | | xy-4x=12 | | 6y-9(5y-8)= | | -3x-8+2x=8 | | 4.6+10m=8.81 | | 3(2x-2)+5=6(x+1) | | -9(v+2)+4v+7=8v+8 | | 76x-9=4x | | -3x+9x-41=97 | | 5x-2=1+3x | | X+21=3X-1 | | 22+6z+95=b | | 2(2x+3x)-10=30 | | 12x^3+6x^2+24x= | | 24/5x5/9 | | 2c+12=3c+c+6 | | -4y+4y=16 | | 2+x/3=-6 | | 3(x+1)=2.4x+22 | | 5a-(8-a)=4a+8 | | -4=7x-1*-8 | | x-9-3x=2x-7 | | 2x=11x+15 | | 5-2x/3=7 | | v^5+64v^3=0 | | 4s-17=25 | | 127+(a+96)=b |